Kajian Pusat Pembelajaran Keluarga (Puspaga) : Sebuah Program Penanggulangan Pergaulan Bebas di Kecamatan Tambaksari Kota Surabaya - Prameswari, Pradiptia Dwi Ayu; Rahaju, Tjitjik (Universitas Negeri Surabaya, 2024)
The implementation of the Family Learning Center Program (Puspaga) is inseparable from the implementation of policies supervised by the Office of Women's Empowerment and Child Protection as well as Population Control and Family Planning. Puspaga is a form of prevention service under the coordinator of Surabaya City DP3APPKB as a form of state concern in improving family life and resilience through education/parenting programs, child protection skills, the ability to increase children's participation in the family and the implementation of counseling programs for children and families. The purpose of this study is to describe the implementation of the Puspaga program in Tambaksari District, Surabaya City. This type of research is descriptive qualitative, which is analyzed with several policy indicators according to George Edward III consisting of communication, resources, disposition, and bureaucratic structure. The subject of this study was DP3APPKB Surabaya City and additional data were obtained from Surabaya City residents who received the program. This research was conducted in DP3APPKB and Tambaksari District, Surabaya City with observation, interview, and documentation techniques. Analyzed by collecting data, reducing data, presenting data and drawing conclusions sourced through primary data and secondary data. The results of the study show that communication between DP3APPKB and policy implementers and the community in program delivery is clear, but for human resources from program implementers are still limited and lack of budget, lack of community participation in participating in Puspaga program socialization activities. Based on the results of the study, suggestions that can be given by researchers in the implementation of the Puspaga program are 1) The delivery of the Puspaga program related to adolescent promiscuity has not been prioritized. 2) Increase the number of human resources implementing the Puspaga program. 3) The role of the community in implementation needs to be improved.